THE QUALITY OF ACCOUNTING INFORMATION IS IMPORTANT TO THE OWNER OF SMALL AND MEDIUM ENTERPRISES (UKM) IN BUTUNG MARKET MAKASSAR CITY - Fitri Anggria Ningsih Sainuddin; Syamsu Alam (Universitas Islam Balitar, 2017)
This study aims to examine whether the understanding of accounting and the application of accounting recording systems has a significant effect on the quality of accounting information, so the information can be used as an important reference in conducting ongoing business evaluations. This research was conducted at the Butung Market in Makassar City. The object of this research is a basic understanding of accounting, application of accounting information systems, and the quality of accounting information. The type of data is quantitative data. The data source is primary data with a Likert scale. The population of this research is Los traders (shops) in Butung Market Makassar city. Determination of the sample is done by probability sampling technique with the simple random sampling method. Data collection was carried out using a questionnaire. The analytical model used is multiple linear regression analysis. The results of this study indicate that: 1) Basic understanding of accounting has a positive and significant influence on the quality of accounting information, it means that the higher level of understanding of the accounting basis of traders more able to provide quality accounting information; 2) The accounting information system has a positive and significant influence on the quality of accounting information, it means that the higher the commitment to implement the accounting system of traders in conducting their business more able to provide quality accounting information; and 3) Simultaneous hypothesis test results (F test) obtained a Fcount value of 17.305> Ftable of 3.29 with a significance level of 0.000 <alpha 0.05, it can be concluded that at a 95% confidence level the basic understanding factors of accounting and accounting information systems are simultaneous significant effect on the quality of accounting information.